Supplementation of H7N9 Virus-Like Particle Vaccine With Recombinant Epitope Antigen Confers Full Protection Against Antigenically Divergent H7N9 Virus in Chickens - Kong, Dexin; Chen, Taoran; Hu, Xiaolong; Lin, Shaorong; Gao, Yinze; Ju, Chunmei; Liao, Ming; Fan, Huiying (Frontiers in Immunology, 2022)
The continuous evolution of the H7N9 avian influenza virus suggests a potential outbreak of an H7N9 pandemic. Therefore, to prevent a potential epidemic of the H7N9 influenza virus, it is necessary to develop an effective cross-protective influenza vaccine. In this study, we developed H7N9 virus-like particles (VLPs) containing HA, NA, and M1 proteins derived from H7N9/16876 virus and a helper antigen HMN based on influenza conserved epitopes using a baculovirus expression vector system (BEVS). The results showed that the influenza VLP vaccine induced a strong HI antibody response and provided effective protection comparable to the effects of commercial inactivated H7N9 vaccines against homologous H7N9 virus challenge in chickens. Meanwhile, the H7N9 VLP vaccine induced robust cross-reactive HI and neutralizing antibody titers against antigenically divergent H7N9 viruses isolated in wave 5 and conferred on chickens complete clinical protection against heterologous H7N9 virus challenge, significantly inhibiting virus shedding in chickens. Importantly, supplemented vaccination with HMN antigen can enhance Th1 immune responses; virus shedding was completely abolished in the vaccinated chickens. Our study also demonstrated that viral receptor-binding avidity should be taken into consideration in evaluating an H7N9 candidate vaccine. These studies suggested that supplementing influenza VLP vaccine with recombinant epitope antigen will be a promising strategy for the development of broad-spectrum influenza vaccines.